The Development of Cases of Acute Respiratory Infections (ARI) in the Mining Environment of PT. Antam Kumoro Village Pomalaa District 2019-2021 - Sukma, Komang Ayi; Azizi Jayadipraja, Erwin; Prasetyo, Mulyadi; Supodo, Timbul; Sunarsih, Sunarsih (Magister Kesehatan Universitas Mandala Waluya, 2022)
Introduction: The mining industry not only has a positive impact on the regional economy but also has an impact on decreasing air quality, which triggers an increase in the incidence of acute respiratory infections (ARI). This study aims to examine the development of ARI cases in the mining environment of PT Antam, Kumoro Village, Pomalaa District in 2019-2021. Method: The research design used is descriptive research with a time series approach. The population and research sample are secondary data on ARI cases in Kumoro Village, Pomalaa District in 2019-2021. Results: The number of ARI cases in 2019 was 179 cases, in 2020 there were 43 cases, and in 2021 there were 70 cases. Conclusion: During 2019-2021, cases of ARI in Kumoro Village, Pomalaa District fluctuated caused of the impact of mining activities